The central role of the Quran in the development of the Islamic educational paradigm - Akhyar, Muaddyl; Batubara, Juliana; Deliani, Nurfarida (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2024)
Education is a matter of life and life (life is education and education is life). The whole process of life and human life is a process of education. This paper is about the verses of the Qur'an that form the paradigm of Islamic education which is motivated by various educational theories and verses about education both the nature and its elements inspire the author to see the extent of the concept of education in the Qur'anic perspective. This paper uses a qualitative method with a library research approach that explores various verses about education in the Qur'an and the relevant ones and then analyzed with a thematic interpretation approach so as to successfully bring up the paradigm of Islamic Education. The results of the study found that the Quran has a role as the main guideline in Islamic education. As the main source of teachings in Islam, the Quran becomes the foundation for the formation of curriculum, teaching methods, values, and the ultimate goal of education. It provides ethical guidance, morality, spiritual values, as well as practical directions in guiding a holistic education, covering intellectual, moral, and social aspects. As a result, the Quran plays a key role in shaping a comprehensive and sustainable paradigm of Islamic education.